Adaptation and validation of the Opinion Scale on Inclusive Education in Early Childhood Education Teachers - Castillo Fuerman, Milagros Marisol (2025)
A relevant aspect influencing inclusive practices is teachers' attitudes and predispositions toward diversity. Understanding their opinions on these issues requires validated, reliable, and appropriate instruments for use in early childhood education. This study describes the adaptation, validation, and reliability process of the instrument for the Opinion Scale on Inclusive Education developed by Bravo and Cardona (2013). This study includes content validation conducted with a team of expert judges, which allowed for the updating of some terms and adaptations of the items to the context. For construct validation and reliability analysis of the instrument, it was administered to a sample of 129 early childhood teachers. The results indicate that the items can be used to gather teachers' opinions about their perceptions and predispositions toward inclusive education. The homogeneity index for all items shows correlations above .20, thus contributing to the measurement of the expected construct. The results showed a Cronbach's alpha of .83 for the total scale, demonstrating the instrument's reliability.